2008
DOI: 10.1007/s12262-008-0077-x
|View full text |Cite
|
Sign up to set email alerts
|

Port site metastasis after laparoscopic cholecystectomy

Abstract: We report a case of 62-year-old woman, who developed port site metastasis one year after undergoing laparoscopic cholecystectomy for calculous cholecystitis. This is only second such report in Indian literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…(Table 1, There are numerous reports of the incidental gallbladder carcinoma detected after laparoscopic cholecystectomy with postoperative port-site metastasis. [6][7][8][9] Maker et al 10 in their study which included 113 patients have found that the incidence of port-site metastases after LC for GBCA is up to 40%. However, there is no consensus regarding the patophysiological mechanisms of metastases.…”
Section: Discusionmentioning
confidence: 99%
“…(Table 1, There are numerous reports of the incidental gallbladder carcinoma detected after laparoscopic cholecystectomy with postoperative port-site metastasis. [6][7][8][9] Maker et al 10 in their study which included 113 patients have found that the incidence of port-site metastases after LC for GBCA is up to 40%. However, there is no consensus regarding the patophysiological mechanisms of metastases.…”
Section: Discusionmentioning
confidence: 99%
“…Differential diagnosis is needed in the presence of abdominal wall hernias and primary neoplastic diseases. 5 The most widely accepted mechanisms of tumor spread through trocar port sites are gallbladder perforations, tumor cell spreads due to the action pneumoperitoneum, the chimney phenomenon, and extraction without gallbladder bag. 3,6 CASE REPORT PRESENTATION This is the case of a 59-year-old man who presented with pain around the umbilical region of 3-day evolution.…”
Section: Recurrence Of Gallbladder Adenocarcinoma In Laparoscopic Tro...mentioning
confidence: 99%
“…is contraindicated. 1,2,3 On the other hand, differential diagnosis is important with other tumors of the abdominal wall 5 .…”
mentioning
confidence: 99%
“…Laparoscopic cholecystectomy is the most effective surgical technique for management of symptomatic gall stone disease. 2 and it comprises the major bulk of operations done by general surgeons in our state. This study aims to document the differences in pathoanatomy of the gall stone disease between Tribals and non-Tribals of Tripura.…”
Section: Introductionmentioning
confidence: 99%